2019
DOI: 10.3389/fpls.2019.00050
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of EST-SSR Markers From RNA-Seq Data in Phyllostachys violascens

Abstract: Bamboo are woody grass species containing important economic and ecological values. Lei bamboo (Phyllostachys violascens) is a kind of shoot-producing bamboo species with the highest economic yield per unit area. However, identifying different varieties of Lei bamboo based on morphological characteristics is difficult. Microsatellites play an important role in plant identification and genetic diversity analysis and are superior to other molecular markers. In this study, we identified 18,356 expressed sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 44 publications
5
25
1
Order By: Relevance
“…3). These frequencies of AG/CT repeats are higher than found for other species such bamboo (17.11%) [12], but less than for Magnolia (37.8%) [11]. High frequencies of AG repeats are also reported for other plant species being suggested that could be related to mutation mechanism of generation of SSRs or selective pressure to particular sequences [9,10,11,13,14].…”
Section: Discussionmentioning
confidence: 60%
“…3). These frequencies of AG/CT repeats are higher than found for other species such bamboo (17.11%) [12], but less than for Magnolia (37.8%) [11]. High frequencies of AG repeats are also reported for other plant species being suggested that could be related to mutation mechanism of generation of SSRs or selective pressure to particular sequences [9,10,11,13,14].…”
Section: Discussionmentioning
confidence: 60%
“…Similar in silico approaches in EST-SSR marker development were performed by other studies focusing on other plants, such as bamboo (Cai et al, 2019), mint (Kumar et al, 2015), castor (Thatikunta et al, 2016), Ethiopian potato (Gadissa et al, 2018) and Elymus species (Zhang et al, 2019). The EST-derived SSR markers generated in this study can be used for functional analysis of R genes, once verified by wet lab experiments.…”
Section: Resultsmentioning
confidence: 91%
“…Deep transcriptome sequencing, which generates quantities of data exponentially, provides comprehensive information and good resources for developing new SSR markers and identifying novel genes [38][39][40]. Currently, a plenty of SSR markers, based on transcriptome sequences, have been successfully developed and used for functional variation detection and gene-related genetic analysis in many organisms, accelerating progress in MAS breedings [41][42][43]. In this study, we rst reported the SSR markers of S. oblata basing transcriptome sequences generated via NGS technologies.…”
Section: Discussionmentioning
confidence: 99%